Green approach to dye wastewater treatment using biocoagulants - Chethana, M.; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Raja, S.; Ranade, Vivek V. (ACS Sustainable Chemistry & Engineering, 2016)
The present study focuses on newer biocoagulants, bioformulations, and the understanding of coagulant behavior with biocoagulants in relation to chemical coagulants. Newer biocoagulants, seeds of Azadirachta indica (AI) and pads of Acanthocereus tetragonus, are discussed along with two known biocoagulants, Moringa oleifera and Cicer arietinum seeds. Dye removal studies were carried out using widely reported Congo red dye to facilitate easy comparison with other conventional coagulants and the effect of various parameters such as initial dye concentration, pH, coagulant dose, etc. are discussed in detail. The use of biocoagulant was found to be highly effective, and up to 99% dye removal was achieved for coagulant doses in the range of 300-1500 mg/L. It was also observed that coagulation is pH sensitive, similar to chemical coagulants. Although the biocoagulant dose is relatively higher than the conventional chemical coagulants, a good value for the sludge volume index, similar to 50 mL/g for 1 h and 30 min, respectively, was obtained for the two coagulants, Acanthocereus tetragonus and Moringa oleifera. A very high particle count compared to chemical coagulants was observed using a focused beam reflectance measurement. Bioformulation with chemical coagulants such as alum, ferric, and aluminum based coagulants can, not only lower doses of biocoagulants (up to one-third) but can also result in significant improvement in the coagulation performance, up to 50% or more.
Keywords: coagulation; dye removal; Effluent treatment; flocculation; pollution

Solvent degradation studies using hydrodynamic cavitation - Suryawanshi, Pravin G.; Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ruparelia, Jayesh P.; Ranade, Vivek V. (Environmental Progress & Sustainable Energy, 2018)
Hydrodynamic cavitation for the degradation of organic solvents was investigated in detail using a newer form of cavitating device-vortex diode. The results were also compared with that using conventional cavitating device orifice. Removal of three different organic solventsacetone, methyl ethyl ketone (MEK), and toluene were studied on a pilot plant with capacity of 1m(3)/h. The effect of different operating parameters such as inlet pressure, initial concentration, and reactor type on the degradation rate of solvent was investigated in detail. The results revealed that efficiency of solvent removal varies substantially with the change in physical operating conditions and nature of the solvent. It was found that up to 80% degradation could be achieved for toluene (cavitational yield 32.2 x 10(-3) mg/J), substantially higher than that for acetone and MEK indicating the effect of molecular weight/structure in the degradation process. Further, the results clearly indicated chemical oxidation as a predominant mechanism for degradation and not physical destruction. Vortex diode that works on the principle of vortex generation for cavitation, was found to be far superior over conventional cavitating device-orifice- approximate to up to eight times higher cavitational yield could be obtained for toluene as compared to orifice. The results of this study provide newer insight into solvent removal using hydrodynamic cavitation and would have bearing on the treatment of solvent containing wastewaters. (C) 2017 American Institute of Chemical Engineers
Keywords: Effluent treatment; industry; pollution; Vortex diode; wastewater